Resourcing and talent management : the theory and practice of recruiting and developing a workforce - Taylor, Stephen (London ; New York : Kogan Page Limited, 2022)
'An essential textbook for the CIPD Level 7 module in Resourcing and Talent Management which covers the recruitment, selection and retention of staff as well as employee retirement, dismissals and redundancy. Resourcing and Talent Management provides broad and accessible coverage of key topics for HR masters students and is the essential companion for the CIPD Level 7 module of the same name. It covers everything from job design and both internal and external recruitment through to interviewing, selection and contracts of employment. There is also guidance on staff retention, succession planning, employee turnover as well as crucial information on how staff leave the business whether this is retirement, redundancy or dismissal. This new edition of Resourcing and Talent Management now includes a brand new chapter on managing absence as well as new content on the UK labour market outside the EU and the implications of Brexit on recruitment and staff development, Fully updated throughout and aligned to the new CIPD qualification framework, this textbook includes'explore further' boxes to encourage students to read more deeply,'pause for thought' boxes to encourage reflection on learning and activities to put their learning in practice and test their understanding'--
Revised edition of the author's Resourcing and talent management, [2019]
Includes bibliographical references (pages 439-463) and index.
Keywords: Personnel management